Accelerating genome editing in CHO cells using CRISPR Cas9 and CRISPy, a web‐based target finding tool. Issue 8 (22nd May 2014) - Ronda, Carlotta; Pedersen, Lasse Ebdrup; Hansen, Henning Gram; Kallehauge, Thomas Beuchert; Betenbaugh, Michael J.; Nielsen, Alex Toftgaard; Kildegaard, Helene Faustrup
ABSTRACT Chinese hamster ovary (CHO) cells are widely used in the biopharmaceutical industry as a host for the production of complex pharmaceutical proteins. Thus genome engineering of CHO cells for improved product quality and yield is of great interest. Here, we demonstrate for the first time the efficacy of the CRISPR Cas9 technology in CHO cells by generating site‐specific gene disruptions in COSMC and FUT8, both of which encode proteins involved in glycosylation. The tested single guide RNAs (sgRNAs) created an indel frequency up to 47.3% in COSMC, while an indel frequency up to 99.7% in FUT8 was achieved by applying lectin selection. All eight sgRNAs examined in this study resulted in relatively high indel frequencies, demonstrating that the Cas9 system is a robust and efficient genome‐editing methodology in CHO cells. Deep sequencing revealed that 85% of the indels created by Cas9 resulted in frameshift mutations at the target sites, with a strong preference for single base indels. Finally, we have developed a user‐friendly bioinformatics tool, named "CRISPy" for rapid identification of sgRNA target sequences in the CHO‐K1 genome. The CRISPy tool identified 1, 970, 449 CRISPR targets divided into 27, 553 genes and lists the number of off‐target sites in the genome. In conclusion, the proven functionality of Cas9 to edit CHO genomes combined with our CRISPy database have the potential to accelerate genome editing and synthetic biology efforts in CHO cells. Biotechnol. Bioeng. 2014; 111: 1604–1616. © 2014 The Authors. Biotechnology and Bioengineering Published by Wiley Periodicals, Inc.